Strengthening Religious Moderation through Islamic Religious Education Values at Public Senior High School 1 Bambanglipuro Bantul - Sihono, Sihono; Cahyo, Septian Dwi (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: This study investigates the enhancement of religious moderation by implementing Islamic religious education values at Public Senior High School 1 Bambanglipuro, Bantul. Employing a descriptive qualitative research design, data were gathered using observations, semi-structured interviews, and document analysis. The research is underpinned by Thomas Lickona's theory of value education, emphasising the role of value education in shaping character and behaviour. Participants included the principal, teachers, and students selected through purposive sampling to provide comprehensive insights. The findings highlight integrating critical Islamic values such as faith, honesty, obedience, and tolerance into the school's curriculum. These values are conveyed through classroom activities, extracurricular programs, and school culture, resulting in notable improvements in student behaviour, reduced inter-religious conflicts, and enhanced attitudes of tolerance and respect. The study underscores the effectiveness of Islamic religious education in promoting religious moderation and fostering a peaceful and pluralistic society. Implications for educational policy and practice are significant, suggesting that incorporating structured moral education can play a crucial role in achieving societal harmony. Recommendations include the nationwide adoption of similar educational programs and ongoing professional development for educators to ensure sustained positive impacts. Future research should expand to include more schools and regions to validate these findings further and explore additional factors influencing the success of religious moderation initiatives in educational settings. Abstrak: Penelitian ini menginvestigasi penguatan moderasi beragama melalui implementasi nilai-nilai pendidikan agama Islam di SMA Negeri 1 Bambanglipuro, Bantul. Dengan menggunakan desain penelitian kualitatif deskriptif, data dikumpulkan melalui observasi, wawancara semi-terstruktur, dan analisis dokumen. Penelitian ini didasari oleh teori pendidikan nilai Thomas Lickona, yang menekankan peran pendidikan nilai dalam membentuk karakter dan perilaku. Partisipan penelitian termasuk kepala sekolah, guru, dan siswa yang dipilih secara purposive untuk memberikan wawasan yang komprehensif. Temuan penelitian menyoroti integrasi nilai-nilai Islam kunci seperti iman, kejujuran, ketaatan, dan toleransi ke dalam kurikulum sekolah. Nilai-nilai ini disampaikan melalui kegiatan kelas, program ekstrakurikuler, dan budaya sekolah, yang menghasilkan perbaikan signifikan dalam perilaku siswa, pengurangan konflik antaragama, dan peningkatan sikap toleransi dan saling menghormati. Penelitian ini menegaskan efektivitas pendidikan agama Islam dalam mempromosikan moderasi beragama dan membangun masyarakat yang damai dan pluralis. Implikasi untuk kebijakan dan praktik pendidikan sangat penting, menyarankan bahwa menggabungkan pendidikan moral yang terstruktur dapat berperan penting dalam mencapai harmoni sosial. Rekomendasi mencakup adopsi program pendidikan serupa secara nasional dan pengembangan profesional berkelanjutan bagi pendidik untuk memastikan dampak positif yang berkelanjutan. Penelitian lebih lanjut harus diperluas untuk mencakup lebih banyak sekolah dan wilayah untuk lebih memvalidasi temuan ini dan mengeksplorasi faktor tambahan yang mempengaruhi keberhasilan inisiatif moderasi beragama di lingkungan pendidikan.